Trump II and US nuclear assurances in the Indo-Pacific: Why Australia, Japan, and South Korea have other concerns - Liviu Horovitz; Elisabeth Suh (Stiftung Wissenschaft und Politik (SWP), 2024)
While heated debates in Europe have focused on how to respond if Donald J. Trump is re-elected to the White House, discussions in Australia, Japan, and South Korea reveal a greater sense of confidence in Washington's commitments. The fear that the United States would withdraw its nuclear assurances is much less pronounced in the Indo-Pacific than in Europe. This serenity appears primarily grounded in a shared understanding that a bipartisan consensus is driving the US commitment to contain China's rise - a goal that requires reliable allies across the Pacific. At the same time, US allies want to maintain the regional status quo and are willing to support Washington's efforts. Trump's potential return does little to change these structural incentives. Instead, Pacific allies fear challenges to the East Asian regional order, challenges that are also relevant for Europe's security and prosperity.
Keywords: 320; Donald Trump; US nuclear assurances; Australia; Japan; South Korea; North Korea; transactional approach; European US allies